The puzzle of Muslim advantage in child survival in India - Sonia Bhalotra; Christine Valente; Arthur van Soest (Institute for the Study of Labor (IZA), 2009)
The socio-economic status of Indian Muslims is, on average, considerably lower than that of upper caste Hindus. Muslims have higher fertility and shorter birth spacing and are a minority group that, it has been argued, have poorer access to public goods. They nevertheless exhibit substantially higher child survival rates, and have done for decades. This paper documents and analyses this seeming puzzle. The religion gap in survival is much larger than the gender gap but, in contrast to the gender gap, it has not received much political or academic attention. A decomposition of the survival differential reveals that some compositional effects favour Muslims but that, overall, differences in characteristics between the communities and especially the Muslim deficit in parental education predict a Hindu advantage. Alternative outcomes and specifications support our finding of a Muslim fixed effect that favours survival. The results of this study contribute to a recent literature that debates the importance of socioeconomic status (SES) in determining health and survival. They augment a growing literature on the role of religion or culture as encapsulating important unobservable behaviours or endowments that influence health, indeed, enough to reverse the SES gradient that is commonly observed.
urn:nbn:de:101:1-20090304418
Keywords: O12; I12; J15; J16; J18; 330; Religion; caste; gender; child survival; anthropometrics; Hindu; Muslim; India; Kindersterblichkeit; Religion; Soziale Schicht; Vergleich; Hinduismus; Islam; Indien